2012
DOI: 10.1016/j.envres.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and season on reduced glutathione concentration and energy reserves of Gammarus roeseli

Abstract: a b s t r a c tAs biomarkers are known to be influenced by biotic and abiotic factors (e.g. gender, temperature), we investigated over a one-year long sampling period, the influence of season and gender on reduced glutathione concentrations and its synthesis in the crustacean amphipod Gammarus roeseli. At the same time, we assessed energy reserves and malondialdehyde levels as toxic biomarker. Results have shown that, in both genders, reduced glutathione concentrations were inversely correlated to water temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 46 publications
2
19
1
1
Order By: Relevance
“…However, our results go further, since we have demonstrated a higher PBDE accumulation in females compared to males. This observation could be explained by the fact that PBDEs are highly lipophilic compounds (K ow ranges from 6.5 to 10; European Union (EU), 2001) and that Gammarid females have higher lipids content than males (Gismondi et al, 2012b). This hypothesis is supported by Viganò et al (2009) who have shown that the accumulation of lower PBDEs is directly related to the lipid content of invertebrates.…”
Section: Pbdes Toxicity and Gammarid Gendersupporting
confidence: 69%
“…However, our results go further, since we have demonstrated a higher PBDE accumulation in females compared to males. This observation could be explained by the fact that PBDEs are highly lipophilic compounds (K ow ranges from 6.5 to 10; European Union (EU), 2001) and that Gammarid females have higher lipids content than males (Gismondi et al, 2012b). This hypothesis is supported by Viganò et al (2009) who have shown that the accumulation of lower PBDEs is directly related to the lipid content of invertebrates.…”
Section: Pbdes Toxicity and Gammarid Gendersupporting
confidence: 69%
“…More efficient detoxification in females was already highlighted in previous studies which have demonstrated higher antitoxic defense (e.g. antitoxic enzymes, antioxidant compounds) in females than males (Sroda and Cossu-Leguille 2011;Gismondi et al 2012;Gismondi et al 2013). Energy reserves in amphipod (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…lipid content) might be one of the contributing factor for the observed gender-biased differences in MXR activity. Indeed, it is well known that females contain higher energy reserves than males (Gismondi et al 2012), probably to ensure reproduction processes (i.e. oogenesis more costly than spermatogenesis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations